First report of Lasiodiplodia theobromae causing stem rot disease of begonia (Begonia x elatior hort.) in Brazil - Fujinawa, Miriam Fumiko [UNESP]; De Carvalho Pontes, Nadson; De Souza, Erica Santos Do Carmo; De Goes, Antonio [UNESP]; Do Vale, Helson Mário Martins (Springer Nature, 2012)
Lasiodiplodia theobromae was found causing stem rot on commercial production of Begonia x elatior in São Paulo, Brazil. Illustrations, morphological and molecular description are provided. Based on the morphology, this fungus was recognized as L. theobromae. However, L. theobromae has high similarity with other Lasiodiplodia species, some of which are not possible to be separated by morphological characters. Molecular identification of the fungus isolated from the infected tissues was conducted. The strain from begonia clustered with other isolates of L. theobromae. This is the first report of the occurrence of L. theobromae on B. elatior. © 2012 Australasian Plant Pathology Society Inc.
Keywords: Begonia; Lasiodiplodia theobromae; Stem rot